Aloe vera (L.) Burm.f.: A Review of Phytochemical Properties and Clinical Applications - Asa Kafatima Zahra; Salwa Nabila; Salsabila Audya; Aprilia Nurhayati; Adhya Zahratu Syita (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
Aloe vera (L.) Burm.f. is a succulent plant that has been widely utilized in traditional and modern medicine. This plant contains various bioactive compounds, including polysaccharides, anthraquinones, vitamins, minerals, enzymes, and amino acids, which contribute to its pharmacological activities. This article aims to present a comprehensive scientific review of the botanical characteristics, phytochemical composition, biological activities, mechanisms of action, and clinical applications of Aloe vera based on published scientific literature. A literature study method was employed by reviewing textbooks, scientific articles, and relevant research reports. The reviewed studies indicate that Aloe vera exhibits significant potential as an anti-inflammatory, antimicrobial, antioxidant, wound-healing agent, and as a supportive therapy for digestive and skin health. With proper processing and standardization, Aloe vera has strong potential for development as a raw material for pharmaceutical, cosmetic, and functional food products.